Pengembangan Modul Hypercontent Perkembangan Peserta Didik untuk Meningkatkan Kemampuan Argumentasi Mahasiswa PGSD - Siti Raihan (Journal on Education, 2023)
The development of the hypercontent module for student development is the development of teaching modules that integrate various learning content with a student-centered learning pattern oriented towards student argumentation abilities. Argumentative ability influences students' understanding of the content of student development material, so it needs to be improved in the learning process. This development aims to develop and determine the feasibility of the hypercontent module for student development for the argumentation abilities of PGSD students. This type of research is development research using the ADDIE framework, namely analysis, design, development, implementation, and evaluation. The product developed was implemented in a small group trial (10 students) with an average response of 4.57 in the excellent category and a large group trial (30 students) to obtain an overall average response of 4.6 in the excellent category. The hypercontent module for student development for PGSD students' argumentation abilities has a decent/good quality category to be applied as a practical digital teaching module for student argumentation abilities.